PENINGKATAN KUALITAS PUBLIKASI ILMIAH DAN PENELITIAN BAGI GURU SMA MELALUI PELATIHAN PEMANFAATAN SOFTWARE ZOTERO - Dwiningsih, Kusumawati; Tukiran, Tukiran; Made Sanjaya, I gusti (Universitas Negeri Surabaya, 2019)
This social responsibility (PKM) activity aims to carry out technical training in the preparation of scientific paper and reference management using the Zotero application in writing scientific paper. This activity is applied to the association of Chemistry teachers in Blitar District. The training and mentoring activities consisted of theory and practice with a composition of 30% for theory and 70% for practice, while the m echanism of the workshop activities included preparation, the seminar, and the training phases. Based on the activities carried out, the results show that the implementation of this social responsibilituy activity went well and smoothly, judging from the fact that most participants were quite able to apply Zotero in making excerpts of scientific paper and enthusiastic participants showed high enthusiasm.